Chosen ones - Roth, Veronica (Houghton Mifflin Harcourt, 2020)
Fifteen years ago, five ordinary teenagers were singled out by a prophecy to take down an impossibly powerful entity wreaking havoc across North America. He was known as the Dark One, and his weapon of choice--catastrophic events known as Drains--leveled cities and claimed thousands of lives. Chosen Ones, as the teens were known, gave everything they had to defeat him. On the tenth anniversary of the Dark One's defeat, something unthinkable happens: one of the Chosen Ones dies. When the others gather for the funeral, they discover the Dark One's ultimate goal was much bigger than they, the government, or even prophecy could have foretold--bigger than the world itself.